Comparison of the effects on glycaemic control and β‐cell function in newly diagnosed type 2 diabetes patients of treatment with exenatide, insulin or pioglitazone: a multicentre randomized parallel‐group trial (the CONFIDENCE study). (5th August 2014) - Xu, W.; Bi, Y.; Sun, Z.; Li, J.; Guo, L.; Yang, T.; Wu, G.; Shi, L.; Feng, Z.; Qiu, L.; Li, Q.; Guo, X.; et al.
Abstract Objective Progressive β‐cell dysfunction hinders the maintenance of glycaemic control in type 2 diabetes, but comparative data on β‐cell‐protective therapies are lacking in the early stage of type 2 diabetes. Here we evaluated the comparative glycaemic efficacy and impact on β‐cell function of three antihyperglycaemic agents that have a β‐cell‐protective effect, exenatide, insulin and pioglitazone, in newly diagnosed patients with type 2 diabetes. Design and methods In this 48‐week, multicentre, parallel‐group study, 416 patients newly diagnosed with type 2 diabetes were randomly assigned 1 : 1 : 1 to receive exenatide, insulin or pioglitazone. The primary end‐point was the change in glycosylated haemoglobin (HbA1c) from baseline. Secondary end‐points included effects on weight, blood pressure, lipid profiles and β‐cell function assessed by homeostasis model assessment, fasting proinsulin:insulin (PI/I), disposition index (DI) and acute insulin response (AIR). Results At week 48, mean [95% confidence interval (CI)] HbA1c changes from baseline were −1.8% (−1.55% to −2.05%) with exenatide, −1.7% (−1.52% to −1.96%) with insulin and −1.5% (−1.23% to −1.71%) with pioglitazone. Treatment differences were −0.20% (95% CI −0.46% to 0.06%) for exenatide versus insulin (P = 0.185), and −0.37% (95% CI −0.63% to −0.12%) for exenatide versus pioglitazone (P = 0.002). Significant improvements from baseline in AIR, PI/I and DI were observed with all treatments, with the greatest improvements in DI, as well as weight, blood pressure and lipid profile, observed with exenatide. Conclusions All three agents showed efficacy regarding glycaemic control and metabolic benefits; however, exenatide showed the greatest efficacy. β‐cell function improved in all treatment groups; hence, early initiation of β‐cell‐protective therapy may halt the decline in β‐cell function in type 2 diabetes.